Palliative laparoscopic hepaticojejunostomy: a single-centre prospective series - Ivanko, O. V.; Skyba, V. V.; Homan, A. V. (General Surgery, 2025)
Objective – to assess the safety and efficacy of palliative laparoscopic hepaticojejunostomy in the management of distal bile duct obstruction. Materials and methods. This single‑centre prospective cohort study included 22 patients with inoperable tumour‑related distal bile duct obstruction. Most participants were men (n=17 (77.3%)) with a mean age of 66.7±9.6 years. Bile duct obstruction was caused by pancreatic head adenocarcinoma (n=18), Vater’s papilla adenocarcinoma (n=2), cholangiocarcinoma (n=1), and duodenal melanoma (n=1). A total of 13 (59%) patients had a history of percutaneous transhepatic cholangiostomy, and 3 (13.6%) had unsuccessful endobiliary stenting attempts. All patients underwent palliative laparoscopic procedures, including Roux‑en‑Y hepaticojejunostomy (side‑to‑side or end‑to‑side) and entero‑enteric anastomosis. The primary endpoint was biliodigestive anastomosis patency without reintervention until death or end of observation. Secondary endpoints included 30‑day mortality, complications classified according to the Clavien–Dindo system, bile leakage defined by the International Study Group of Liver Surgery (ISGLS), length of hospitalization, time to resumption of enteral nutrition, and overall survival. Results. The average duration of the operation was 354.5±110.1 minutes with an average blood loss of 58.3±43.1 ml. Complications occurred in 8 (37.5%) patients, including bile leakage in 7 cases (ISGLS B – in 6, ISGLS C – in 1 with biliary peritonitis), and one Clavien–Dindo IIIb event (torsion of the small intestine around the entero‑enteric anastomosis). No cases of wound infection or postoperative bleeding were recorded. The average length of hospitalization was 10.3±5.3 days (range, 4 – 24 days). Most patients (n=19 (86.3%)) were mobilized on the 1st postoperative day, and oral nutrition was initiated on the 2nd day. During the follow‑up period (median – 8.5 months, IQR 6.8 – 12.0), no recurrences of bile duct obstruction or need for repeated drainage were observed. Two episodes of acute cholangitis were managed conservatively. No deaths occurred within 30 days postoperatively. Conclusions. Laparoscopic hepaticojejunostomy appears to be a feasible and effective palliative procedure for distal biliary obstruction in selected patients. This approach maintains anastomotic patency without the need for reintervention, is associated with low blood loss, and enables rapid resumption of enteral nutrition. The complication profile is primarily characterized by manageable bile leakage, with rare Clavien–Dindo grade IIIb adverse events. This method may be considered as an alternative to stenting when stenting is not possible or has failed, or in patients with a life expectancy >6 months who are scheduled for chemotherapy.